Uji Aktivitas Antidiabetes Infusa Daun Sukun (Artocarpus altilis) Pada Mencit Putih Jantan (Mus musculus) Yang Diinduksi Aloksan - Kanne Dachi; Muharni Sahputri; Khaira Ulfida Afrida (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Diabetes mellitus is a degenerative disease and has become a national as well as international health problem. An unhealthy lifestyle is a primary trigger for the onset of diabetes. Synthetic antidiabetic drugs are one therapeutic option, but their side effects lead patients to switch to natural remedies, such as using breadfruit leaves (Artocarpus altilis) by consuming their decoction. Therefore, this study aims to investigate the potential of breadfruit leaves as an antidiabetic agent in vivo. This experimental research used mice as the test animals. Identification of the plant and test animals was conducted. Subsequently, simplicia powder from the breadfruit leaves was produced and its secondary metabolites were identified. Test preparations, including alloxan suspension, metformin suspension, Na-CMC suspension, and breadfruit leaf infusion, were then prepared. Five treatment groups were established, each consisting of 3 mice. The mice were induced with diabetes, and their blood glucose levels were checked over 15 days, with the data analyzed statistically. The results confirmed the validity of the breadfruit plant and the mice. The identification of secondary metabolites showed positive results for alkaloids, flavonoids, glycosides, tannins, and saponins. The 15% breadfruit leaf infusion significantly reduced blood glucose levels (p < 0.05), and its effect was not significantly different from metformin. This indicates that the 15% concentration demonstrated the most potent antidiabetic effect among the three concentrations tested. However, the interpretation of these results is limited by the small sample size in this preliminary study. In conclusion, the 15% breadfruit leaf infusion has the potential to be developed as a herbal antidiabetic agent.